The Effect of Antithrombin III on the Activity of the Coagulation Factors VII, IX and X - Østerud, B; Miller-Andersson, M; Abildgaard, U; Prydz, H (Thrombosis and Haemostasis, 1976)
Antithrombin III, purified to homogeneity according to Polyacrylamide gel disc electrophoresis and immunoelectrophoresis, inhibited the activity of purified factor IXa and Xa, whereas factor VII was not inhibited either in the active or in the native form.Antithrombin III is the single most important inhibitor of factor Xa in plasma. Factor Xa does not, however, reduce the activity of antithrombin III against thrombin.